lncRNA DIGIT and BRD3 protein form phase-separated condensates to regulate endoderm differentiation - Daneshvar, Kaveh; Ardehali, M. Behfar; Klein, Isaac A.; Hsieh, Fu-Kai; Kratkiewicz, Arcadia J.; Mahpour, Amin; Cancelliere, Sabrina O. L.; Zhou, Chan; Cook, Brett M.; Li, Wenyang; Pondick, Joshua V.; Gupta, Sweta K.; et al. (Nature cell biology, 2020)
Cooperation between DNA, RNA and protein regulates gene expression and controls differentiation through interactions that connect regions of nucleic acids and protein domains and through the assembly of biomolecular condensates. Here, we report that endoderm differentiation is regulated by the interaction between the long non-coding RNA (lncRNA) DIGIT and the bromodomain and extraterminal domain protein BRD3. BRD3 forms phase-separated condensates of which the formation is promoted by DIGIT, occupies enhancers of endoderm transcription factors and is required for endoderm differentiation. BRD3 binds to histone H3 acetylated at lysine 18 (H3K18ac) in vitro and co-occupies the genome with H3K18ac. DIGIT is also enriched in regions of H3K18ac, and the depletion of DIGIT results in decreased recruitment of BRD3 to these regions. Our findings show that cooperation between DIGIT and BRD3 at regions of H3K18ac regulates the transcription factors that drive endoderm differentiation and suggest that protein–lncRNA phase-separated condensates have a broader role as regulators of transcription. Daneshvar et al. show that BRD3 and the lncRNA DIGIT form phase-separated condensates at genomic regions with H3K18ac to co-regulate the transcription of genes that drive endoderm differentiation.